The influence of simulated pressure changes on the behavior of Larimichthys crocea during the deep sea submarine descent of net cages - Tong, Tong; Yang, Xu; Gui, Fukun; Hu, Jiajun; Niu, Shuai; Tang, Lianghao; Huang, Hengda; Jiang, Yucheng (Frontiers in Marine Science, 2024)
In the process of ascending and descending in deep-sea submerging and lifting cage nets, accompanied by changes in water pressure, pressure is one of the crucial environmental factors affecting the physiology and growth of fish. It directly relates to the comfort of farmed fish in the cage, thereby influencing the quality of aquaculture, especially for high-demanding species on the culture environment like the Larimichthys crocea. Investigating the stress level changes exhibited by L.crocea under environmental pressure variations, understanding the limit tolerance pressure, and its changes, can provide a theoretical basis for the design, application, and increased production of deep-sea submersible cage nets and L.crocea aquaculture. This study explores the effects of varying submersion depths (0–20 m) and speeds (0.6, 1, 1.3, 2, 4 m/min) on the behavioral responses of L.crocea in deep-sea cage environments. Key findings demonstrate that increased submersion depths and speeds significantly influence the physical behaviors and stress responses of the species. At submersion depths of 15 meters and 20 meters, the average swimming speed of the L.crocea exceeds 0.05 meters per second, the tail movement frequency is 1.42 times that of normal pressure, and the gasping frequency exceeds 20%., and at the highest speed of 4 m/min, the swimming speed reaches 0.0902 m/s—3.76 times greater than under normal pressure. The study determines that a submersion depth of 10 meters and a submersion speed of 0.6 meters per minute can minimize stress responses, providing critical insights for optimizing deep-sea aquaculture operations of L.crocea. These results offer valuable guidelines for the design and management of submersible cage systems.